Neural mechanisms of suboptimal decisions - Chau, K; Ka Hung Bolton CHAU (2014)
Making good decisions and adapting flexibly to environmental change are critical to the survival of animals. In this thesis, I investigated neural mechanisms underlying suboptimal decision making in humans and underlying behavioural adaptation in monkeys with the use of functional magnetic resonance imaging (fMRI) in both species. In recent decades, in the neuroscience of decision making, there has been a prominent focus on binary decisions. Whether the presence of an additional third option could have an impact on behaviour and neural signals has been largely overlooked. I designed an experiment in which decisions were made between two options in the presence of a third option. A biophysical model simulation made surprising predictions that more suboptimal decisions were made in the presence of a very poor third alternative. Subsequent human behavioural testing showed consistent results with these predictions. In the ventromedial prefrontal cortex (vmPFC), I found that a value comparison signal that is critical for decision making became weaker in the presence of a poor value third option. The effect contrasts with another prominent potential mechanism during multi-alternative decision making – divisive normalization – the signatures of which were observed in the posterior parietal cortex. It has long been thought that the orbitofrontal cortex (OFC) and amygdala mediate reward-guided behavioural adaptation. However, this viewpoint has been recently challenged. I recorded whole brain activity in macaques using fMRI while they performed an object discrimination reversal task over multiple testing sessions. I identified a lateral OFC (lOFC) region in which activity predicted adaptive win-stay/lose-shift behaviour. In contrast, anterior cingulate cortex (ACC) activity predicted future exploratory decisions regardless of reward outcome. Amygdala and lOFC activity was more strongly coupled for adaptive choice shifting and decoupled for task irrelevant reward memory. Day-to-day fluctuations in signals and signal coupling were correlated with day-to-day fluctuations in performance. These data demonstrate OFC, ACC, and amygdala each make unique contributions to flexible behaviour and credit assignment.